Upaya Meningkatkan Prestasi Belajar Matematika Tentang Pengurangan dengan Model Pembelajaran Kontekstual Siswa Kelas 1 Semester II Sekolah Dasar - Sunarsih, Sunarsih (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2018)
Abstract. This classroom action research is motivated by the low mathematics learning outcomes, especially in the reduction material. This study aims to improve student learning outcomes on Mathematics about the reduction by using contextual learning models are expected to improve student learning outcomes. The contextual learning method is a learning concept that helps teachers associate the material they teach with real-world student situations and encourage students to make connections between the knowledge he has and its applicationin their daily lives. The method used in this study is Classroom Action Research (PTK) with the object of research in class I SD Negeri 2 Gatak. The focus of the research on the reduction of contextual learning is an effort to improve the learning outcomes of Mathematics. Data collection is done by direct observation of the learning process. The results showed that there was a significant increase of student learning outcomes in pre-cycle learning activities, cycle I and cycle II. The increase can be seen from the average value of students and the percentage of completeness of learning outcomes from KKM which is determined at 65. Based on the results of these observations it can be concluded that the application of Mathematics subject matter reduction learning contextual learning models can improve student learning outcomes in class ISD Negeri 2 Gatak. Furthermore, the results of this study can be used to improve learning with similar cases.